Persatuan Indonesia yang Rawan - PJ. Suwarno (Unisia, 2003)
It is generally understood that to unite thousands of Indonesian island to be an integrated state underthesole control of the centralistic government in Jakarta is far from easy. Therefore, the solution is, the government should empower the unifying factors through three ways, first, the central government must provide enough telecommunication as well as transportation systems. Secondly, the government must enhance the level of readiness of thepeople to respect other people regardless with any reasons for discrimination. Thirdly, the government must make any efforts to gain economical justice among people.